(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Personal reflexive activity should not be focused only on knowledge of one academic subject, but should be focused on many aspects, and the student’s reflexive ability should be evaluated not by one person, but by many. Generalized reflection implies the analysis of the behavior of the teacher-pedagogue during the lesson by the students and the formation of a general conclusion of the student group as a result of the analysis. It is recommended to conduct the reflection of the emotional state before the beginning of the lesson, to ensure the establishment of relationships between the participants of the educational process in accordance with the educational goals.Reflection of practical activity allows to determine the form, method and style of the lesson suitable for the essence of the subject in order to master the educational material provided for in the plan of the lesson. The application of this type of reflection at the end of the lesson serves as a necessary criterion for evaluating the activities of students during the lesson.